1997
DOI: 10.1021/jp961671f
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of Nonamphiphilic 2,2‘-p-Phenylenebis(5-phenyloxazol) (POPOP) Assembled in Supramolecular Langmuir−Blodgett Films

Abstract: This paper reports the incorporation of a nonamphiphilic blue laser dye 2,2′-p-phenylenebis(5-phenyloxazol), abbreviated as POPOP, in Langmuir-Blodgett (LB) films mixed with stearic acid (SA) and their spectroscopic properties. The surface pressure versus area per molecule isotherms of POPOP mixed with SA at different molar ratios reveal a plateau-like region that suggests reorientation of the POPOP molecules from lying flat at the air-water interface to an almost vertical alignment. Miscibility studies indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 99 publications
0
22
0
Order By: Relevance
“…It is interesting to note that the spectroscopic and aggregation behaviour of non-amphiphilic blue laser dye 2, 2 0 -p-phenylene bis (5-phenyl oxazol) (POPOP) on the restricted geometry of LB films have been reported by Dutta [14]. Spectroscopic analysis confirms the formation of microcrystallites of POPOP in the LB films.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is interesting to note that the spectroscopic and aggregation behaviour of non-amphiphilic blue laser dye 2, 2 0 -p-phenylene bis (5-phenyl oxazol) (POPOP) on the restricted geometry of LB films have been reported by Dutta [14]. Spectroscopic analysis confirms the formation of microcrystallites of POPOP in the LB films.…”
Section: Introductionmentioning
confidence: 73%
“…Non-amphiphilic molecules are not ideally suited for thin film deposition by this technique. However, some recent works [10][11][12][13][14][15][16][17] showed that highly organized LB films of these materials can be formed, when a long-chain fatty acid or some inert polymer matrix was used as the supporting medium. Since these non-amphiphilic molecules are easily available and have wide varieties having different interesting physical properties, hence a lot of investigations on LB films using these molecules are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…30 Monolayers of nonamphiphilic molecules are instable and cannot be transferred onto solid substrates. 30 Monolayers of nonamphiphilic molecules are instable and cannot be transferred onto solid substrates.…”
Section: Phase States Of Psc and Psc-nr Monolayers At Water-air Intermentioning
confidence: 99%
“…It is known that for nonamphiphilic dyes that are insoluble in water, e.g., for oxazines dyes, it is possible to record a isotherm of monolayer compression on phase interface. 30 Monolayers of nonamphiphilic molecules are instable and cannot be transferred onto solid substrates. 6,30 It was observed (Figure 3, curve 2) that pure NR at the air-water interface does not form stable monolayer and surface pressure rise from an initial ''zero'' value to about 20 mN m À1 .…”
Section: Phase States Of Psc and Psc-nr Monolayers At Water-air Intermentioning
confidence: 99%
“…All these fluors have high absolute photoluminescence (PL) yields. 4,[10][11][12] The solvatochromic characteristics of these fluors have been studied comprehensively in different non-polar and polar solvents, solid solvents such as thin-films, different polymer environments and in thin-films. 2,10-15 Coumarin 6 is a benzopyrone-class dye with a dialkyl-substituted amino-group and a benzothiazole-group asymmetrically placed around a lactone-ring.…”
Section: Introductionmentioning
confidence: 99%